Comparative evaluation of ultrasound and fluoroscope guided intra-articular sacroiliac joint injection in patients with sacroiliac joint pain - Kanika; Amit Kumar; Naveen Malhotra; Anshul; Jyotsna; Navya Malhotra (Asian Journal of Medical Sciences, 2024)
Background: Tissues which transmit pain in the lower back include disc, nerve root, dura, muscles, ligaments, facet joints, and sacroiliac joint (SIJ). The SIJ contributes around 13–30% in patients with chronic low back pain. The SIJ is difficult to enter with a needle because of its complex configuration. Ultrasound and fluoroscopy are the two tools which guide in performing SIJ injections. Aims and Objectives: The SIJ is susceptible to arthritis, trauma, and degeneration which lead to pain and dysfunction. Intra-articular SIJ injections (IASIJIs) have diagnostic and therapeutic value and have been administered for the treatment of SIJ pain. Materials and Methods: Sixty patients (aged 20–60 years) with pain patterns consistent with SIJ pain who did not respond to conservative treatment were included in the study. The patients were randomly divided into two groups of 30 each: Group U (n=30): Ultrasound-guided IASIJI and Group F (n=30): Fluoroscope-guided IASIJI. A total of 3 mL drug solution comprising 1 mL of 0.25% bupivacaine plus 2 mL of methylprednisolone (80 mg) was injected in both groups. Results: There was a statistically significant improvement in pain scores after IASIJI in both groups. The change in pain score was significantly more in Group F as compared to Group U at 3 and 6 months after IASIJI. Two weeks after IASIJI, the mean pain score in both groups remained < 2 at all time intervals throughout the study period. The variation in the Oswestry Disability Index (ODI) at different time intervals when compared to ODI before injection in both the groups was clinically and statistically significant (P<0.001). The change in ODI was more in Group F as compared to Group U at all time intervals. Excellent patient satisfaction was reported by the majority of the patients at different time intervals in both groups. Conclusion: Both techniques were effective and provided good pain relief to the patients with SIJ pain. Fluoroscope-guided SIJ injection is better than ultrasound-guided SIJ injection in terms of improvement in pain score and functional disability.